Porites Coral on a Remote Reef Reveal Marine Phosphorus Biogeochemical Cycling Following Artificial Disturbance. Issue 8 (3rd August 2020) - Jiang, Wei; Yang, Haodan; Yu, Kefu; Song, Yinxian; Zhao, Jian‐xin; Feng, Yue‐xing; Han, Tao; Wu, Xingyuan; Ning, Zhiming; Xu, Shendong; Wang, Yinghui
Abstract: Excess anthropogenic phosphorus (P) supplied to marine systems, which may subsequently jeopardize ecosystem structure and function, has altered the P balance and quadrupled its flow. However, due to the diversity of P sources, the unpredictability and variability of human activities, and the absence of long‐term records, it remains uncertain how long the effects of excess P persist in aquatic ecosystems, and whether it stimulates gross primary productivity. In this study, we utilized geochemical proxies in coral skeletons from an atoll in the Xisha Islands of the South China Sea to reconstruct historical patterns of P in surface seawater. This atoll has remained in a natural state for an extended period of time, except for a short period of unambiguously documented guano extraction. Analyses of coral skeletons dating back to 1851 CE distinctly show that the P concentration in surface seawater increased abnormally in the 1960s. We deduced that guano extraction at that time led to an abrupt increase in the long‐term equilibrium of seawater P concentration. Subsequent P addition appeared to have continued for at least 30 years after phosphorite exploitation ceased, and P showed a decay period that was longer than that of other elements. Similar temporal trends of coral P/Ca and δ 13 C indicated that elevated marine primary productivity was associated with increased P. Large inputs within a short period, as well as the continued influence of P over the long term, can serve as a natural ecological analog for coral reefs subject to nutrient contamination. Plain Language Summary: Nutrient contamination in tropical islands is considered a major cause of declines in the health of coral reefs. However, without a long‐term record, it is difficult to determine nutrient variations in the surface seawater clearly. Using P/Ca ratios in the aragonite layer of Porites lutea coral, we found that there was an abnormal increase in P concentrations in surface seawater surrounding Yongxing Island, of the Xisha Islands of the South China Sea, in the 1960s. We inferred that this phenomenon was related to the government's exploitation of guano. Since then, these P have continued to precipitate from the surface waters of nearby coral reefs for at least 30 years. This trend differs from that of other elements (this included the time taken for P from the island to reach seawater after exploitation of the guano). In addition, we found that coral δ 13 C peaked and changed in line with P/Ca during the 1960s to 2005. Large inputs of P and long‐term persistent effects in the Xisha Islands can be used as a natural ecological simulation, similar to other coral reefs that have become eutrophic by anthropogenic activities. Key Points: Phosphorus input from guano extraction had a significant stress on remote coral reefs Prolonged elevated P in seawater were related to its involvement in productivity Excess P in seawater persisted for 30 years after the artificial disturbance